Responses to linguistic and cultural diversity in New Zealand state secondary schools : a qualitative study : a thesis presented in partial fulfilment of the requirements for the degree of Doctor of Philosophy in Applied Linguistics at Massey University, Manawatū, New Zealand - McCarthy, Geraldine Anne (Massey University, 2019)
Demand for English language learning (ELL) in New Zealand has intensified since the millennium, alongside marked increases in immigration to cater for businesses such as construction and agriculture, and the impacts of episodic earthquake damage. ELL assistance in state secondary schools in New Zealand is centred on the dynamics surrounding English for Speakers of Other Languages (ESOL) departments. This study seeks to gain an understanding of the layered contexts surrounding and within ESOL Departments by using a conceptual framework of ecology and a qualitative, case study paradigm. It draws on data from interviews, observations, documentation and researcher journaling to examine ESOL Department systems and practices in three state secondary schools with differing locations, deciles and ESOL Department structures. The findings reveal the significant weight of wide-ranging regulatory and ideological interactions connected with ESOL Departments associated with colonial aspirations, ‘Tomorrow’s Schools’ legislation and New Zealand’s bicultural status. Findings also highlight the affordances and constraints experienced in ELL by staff and students in the case study schools and explore the costs and benefits as set against the pressures of local, national and international dynamics. The study concludes with implications for personnel responsible for ELL at national and local levels. It calls for more professional development initiatives and specific ELL regulation of resources for educationalists to assist with ELL linguistic, social and cultural integration. Results are intended to enhance ELLs’ educational opportunities in schools as well as contribute to efforts for increased social cohesion between people of diverse ethnicities in this rapidly diversifying nation.
Keywords: English language; Study and teaching (Secondary); New Zealand; Foreign speakers; School management and organization; High schools; 470401 Applied linguistics and educational linguistics